Characterization of a Novel Simian Immunodeficiency Virus with a vpu Gene from Greater Spot-Nosed Monkeys (Cercopithecus nictitans) Provides New Insights into Simian/Human Immunodeficiency Virus Phylogeny - Courgnaud, Valérie (American Society for Microbiology, 2002)
In the present study, we describe a new simian immunodeficiency virus (SIV), designated SIVgsn, naturally infecting greater spot-nosed monkeys (Cercopithecus nictitans) in Cameroon. Together with SIVsyk, SIVgsn represents the second virus isolated from a monkey belonging to the Cercopithecus mitis group of the Cercopithecus genus. Full-length genome sequence analysis of two SIVgsn strains, SIVgsn-99CM71 and SIVgsn-99CM166, revealed that despite the close phylogenetic relationship of their hosts, SIVgsn was highly divergent from SIVsyk. First of all, they differ in their genomic organization. SIVgsn codes for a vpu homologue, so far a unique feature of the members of the SIVcpz/human immunodeficiency virus type 1 (HIV-1) lineage, and detailed phylogenetic analyses of various regions of the viral genome indicated that SIVgsn might be a mosaic of sequences with different evolutionary histories. SIVgsn was related to SIVsyk in Gag and part of Pol and related to SIVcpz in Env, and the middle part of the genome did not cluster significantly with any of the known SIV lineages. When comparing the two SIVgsn Env sequences with that of SIVcpz, a remarkable conservation was seen in the V3 loop, indicating a possible common origin for the envelopes of these two viruses. The habitats of the two subspecies of chimpanzees infected by SIVcpz overlap the geographic ranges of greater spot-nosed monkeys and other monkey species, allowing cross-species transmission and recombination between coinfecting viruses. The complex genomic structure of SIVgsn, the presence of a vpu gene, and its relatedness to SIVcpz in the envelope suggest a link between SIVgsn and SIVcpz and provide new insights about the origin of SIVcpz in chimpanzees.